The pneumatology of Paul Tillich and Arnold van Ruler - Hodnett, GD (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
Pneumatology is the link between Christology and eschatology. Pneumatology must be related to and distinguished from both Christology and eschatology. The Spirit is the power of the Word and the Word is the form of the Spirit. In this sense there is a point of identity between pneumatology and Christology: every manifestation of the Spirit stands under the criterion of the revelation given in Christ. But pneumatology cannot be reduced to Christology as, in the Spirit, we are not replaced but rather taken into a relationship with God. This relationship is to be understood eschatologically, because the work of the Spirit is to express God’s eschatological intentions in us. However, pneumatology cannot simply be identified with eschatology. This relationship with God is a matter of the struggle of the Spirit with the flesh – there is no perfectionism. Tillich and Van Ruler complement each other in their discussion of this multifaceted understanding of the position and work of the Holy Spirit.